Engaging Pre-Service Teachers in Interactive Social Justice-Themed Read-Alouds - Kayln Hoppe (Educational Considerations, 2022)
This qualitative case study explored how pre-service teachers responded to social justice-themed picture book read-alouds in an undergraduate literacy course. Data were collected from personal observations, semi-structured focus group interviews, and student work, and were analyzed using inductive analysis. Findings indicate how reading multicultural literature aloud plays an important role in post-secondary students’ content understanding and preparation for a career in teaching. This case study may inspire teacher educators to incorporate multicultural read-alouds into higher education coursework.
Keywords: higher education; teacher preparation; elementary education; literacy instruction; social justice